Public Library Digital Competency Mapping 2019: A Survey on Digital Skills of Library Professionals With Different Qualifications - Borbély, Mária (Frontiers in Education, 2022)
Social science researchers rarely can repeat a representative empirical study on an essentially identical sample in a relatively short time, and thus to confirm the validity or, on the contrary, the invalidity of the initial results. In the framework of the EFOP-3.3.3-VEKOP-16-2016-00001 "Museum and Library Development for All" grant scheme in Hungary, the flagship project "My Library", implemented under the auspices of the Szabó Ervin Library in Budapest, allowed for two surveys to be conducted two years apart to assess the digital competence status of library professionals working in public libraries. This study seeks to answer the question of the impact of different educational levels on digital competence levels. Furthermore, it asks whether the results of the 2019 survey confirm the findings from 2017 that a higher education librarian degree, the librarian diploma, has a strong competence-increasing effect in each of the digital competence areas. Both studies are representative of the Hungarian public library sector. In the 2017 survey, 1,786 library professionals from different municipal libraries participated, and in the 2019 survey, 1,868. As a result of the survey, an extremely rich data set is available, which allows for an accurate understanding of the digital skills of library professionals, the identification of areas for improvement, or even the organization of targeted professional training.